Validation of organisational learning models: theoretical framework and empirical analyses of five Australian manufacturing organisations. (5th May 2005) - Kayis, Berman; Paipetis, Nikos
The successful transformation of any organisation toward Total Quality Management (TQM) requires an essential role for "learning". Crossing this new frontier requires adaptive behaviours and commitment to effectively change the organisation based on the philosophy of TQM. Such a change is challenging especially in small- to medium-size organisations due to financial and resource limitations. The aim of this paper is to explore the key attributes that may enable manufacturers to become successful learning organisations. The paper is based on five case studies in which the TQM implementation was in place for at least three years. The characteristics of the learning organisations are described followed by discussing the results gathered from manufacturing organisations. The results from the survey are analysed along three lines through which learning in organisations occur; the individual, the team and the organisational levels. Two sets of questionnaires were used to gather feedback from managers and shop floor employees. Background of the organisation, quality practices, team formation, training, communication and reward systems in place are covered to identify strengths and weaknesses of the organisations. The paper concludes with few but vital attributes required for creating successful learning organisations.